2023
DOI: 10.1002/csc2.20890
|View full text |Cite
|
Sign up to set email alerts
|

Wheat stubble height effects on subsequent corn and grain sorghum crops

Abstract: For sustainable productivity, a winter wheat (Triticum aestivum L.)-summer crop (corn [Zea mays L.] or grain sorghum [Sorghum bicolor L.])-fallow (W-SC-F) cropping system could benefit from optimal wheat stubble cutting height management, but only limited information is available. The objective of this study was to evaluate the effect of wheat stubble height on subsequent corn and grain sorghum yields, available soil water, crop water use, and precipitation storage efficiency in a W-C-F and W-S-F cropping syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, estimated optimal N application rates stayed relatively constant across environments in this study unlike variable application rate recommendations by a few prior studies (Qiu et al., 2022; Ren et al., 2022). Most common fertilizer rate to winter wheat recommended or used by researchers are about 90 kg ha −1 in Oklahoma (Thomason et al., 2000), 75–86 kg ha −1 around Tribune (Schlegel et al., 2018, 2023), and 84 kg N ha −1 around Colorado (Halvorson et al., 2004). Therefore, the agronomic and economic optimal rate we found in this study are within those reported for studies in the central Great Plains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, estimated optimal N application rates stayed relatively constant across environments in this study unlike variable application rate recommendations by a few prior studies (Qiu et al., 2022; Ren et al., 2022). Most common fertilizer rate to winter wheat recommended or used by researchers are about 90 kg ha −1 in Oklahoma (Thomason et al., 2000), 75–86 kg ha −1 around Tribune (Schlegel et al., 2018, 2023), and 84 kg N ha −1 around Colorado (Halvorson et al., 2004). Therefore, the agronomic and economic optimal rate we found in this study are within those reported for studies in the central Great Plains.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) reported that an RT system had a 12% yield advantage in dryland wheat in the central Great Plains compared with CT. Other research showed a 15%–18% yield advantage for RT compared with wheat yields in CT system when weeds were removed from RT (Hofmeijer et al., 2019). Among factors that contributed to reported yield benefits from RT wheat are improvement in soil properties, increased retention of soil moisture, and improved water availability to crops (Hofmeijer et al., 2019; Holland, 2004; Meurer et al., 2018; Schlegel et al, 2023). An increase in soil N content in RT than in CT was reported, but yields were compared between these tillage systems with similar fertilizer amounts in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%
“…age in the central Great Plains, contributing to soil water conservation needed for successive crops (Schlegel et al, 2023). However, a recent study reported that the frequency of hot-dry-windy weather events has increased in Kansas and surrounding regions and is attributed to significant yield reduction (Zaho et al, 2022).…”
Section: Core Ideasmentioning
confidence: 99%
“…Presently, major crop rotations in the region, such as wheat–summer crop–fallow, has wheat as the base crop (Assefa et al., 2014; Hansen et al., 2012). In part, because wheat stubble provides excellent soil cover to minimize wind and water erosion and improve soil water storage in the central Great Plains, contributing to soil water conservation needed for successive crops (Schlegel et al., 2023). However, a recent study reported that the frequency of hot‐dry‐windy weather events has increased in Kansas and surrounding regions and is attributed to significant yield reduction (Zaho et al., 2022).…”
Section: Introductionmentioning
confidence: 99%